A Cultivar-Sensitive Approach for the Continuous Monitoring of Olive (Olea europaea L.) Tree Water Status by Fruit and Leaf Sensing - Scalisi, Alessio; Marino, Giulia; Marra, Francesco Paolo; Caruso, Tiziano; Lo Bianco, Riccardo (Frontiers in Plant Science, 2020)
Sustainable irrigation is crucial to reduce water use and management costs in modern orchard systems. Continuous plant-based sensing is an innovative approach for the continuous monitoring of plant water status. Olive (Olea europaea L.) genotypes can respond to drought using different leaf and fruit physiological and morphological mechanisms. This study aimed to identify whether fruit and leaf water dynamics of two different olive cultivars were differently affected by water deficit and their response to changes of midday stem water potential (Ψstem), the most common indicator of plant water status. Plant water status indicators such as leaf stomatal conductance (gs) and Ψstem were measured in the Sicilian olive cultivars Nocellara del Belice (NB) and Olivo di Mandanici (MN), in stage II and III of fruit development. Fruit gauges and leaf patch clamp pressure probes were mounted on trees and their raw data were converted in relative rates of fruit diameter change (RRfruit) and leaf pressure change (RRleaf), sensitive indicators of tissue water exchanges. The analysis of diel, diurnal and nocturnal fluctuations of RRfruit and RRleaf highlighted differences, often opposite, between the two cultivars under water deficit. A combination of statistical parameters extrapolated from RRfruit and RRleaf diurnal and nocturnal curves were successfully used to obtain significant multiple linear models for the estimation of midday Ψstem. Fruit and leaf water exchanges suggest that olive cultivar can either privilege fruit or leaf water status, with MN likely preserving leaf water status and NB increasing fruit tissue elasticity under severe water deficit. The results highlight the advantages of the integration of fruit and leaf water dynamics to estimate plant water status and the need for genotype-specific models in olive.